Refractive Errors in School Going Children – Data from A School Screening Survey Programme - Harpal Singh; V K Saini; Akhilesh Yadav; Bharti Soni (National Journal of Community Medicine, 2013)
Background: The prevalence of blindness in children ranges from approximately 0.3/1000 children in affluent regions to 1.5/1000 in the poorest communities. the importance of early detection and treatment of ocular diseases and visual impairment in young is obvious.